A NiCuZn soft ferrite material and its preparation method and application

By adding auxiliary component B to NiCuZn ferrite material to change the sintering density and microstructure, the problem of high sintering temperature and low sintering performance in the prior art is solved, and high current saturation characteristics and excellent sintering performance are achieved at low temperatures. effect.

CN116730720BActive Publication Date: 2025-02-11GUANGDONG FENGHUA ADVANCED TECHNOLOGY (HOLDING) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310506107.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-08
Publication Date
2025-02-11
Estimated Expiration
2043-05-08

AI Technical Summary

Technical Problem

It is difficult to obtain high current saturation characteristics at high sintering temperatures, and the sintering performance is low, making it difficult to adapt to existing production processes and equipment.

Method used

By adding auxiliary component B to main component A, the sintering density of the parent-phase ferrite material is changed, the liquid-phase sintering mechanism is used to reduce the sintering activation energy, improve the sintering density, and affect the microscopic shape by regulating the component content of auxiliary component B and structural structure, optimize electromagnetic physical properties.

Benefits of technology

Achieve high volume density NiCuZn ferrite material at lower temperatures, improve sintering performance, improve current saturation characteristics and welding resistance rate, and is suitable for high-frequency and miniaturized inductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116730720B_ABST
    Figure CN116730720B_ABST
Patent Text Reader

Abstract

The invention discloses a NiCuZn soft ferrite material and its preparation method and application, which relate to the field of ferrite materials. The NiCuZn soft ferrite material includes a main component A and an auxiliary component B; the main component A includes Fe2O3, ZnO, NiO, CuO, Co3O4; the auxiliary component B includes SiO2, CaCO3, Al2O3, and Na2CO3. The doping amount of the auxiliary component B in the present application can effectively change the sintering density of the parent phase ferrite material, and the magnetic permeability, densification degree, microstructure, basic electromagnetic properties and stability of the ferrite material at a low temperature sintering temperature are improved, and the sintering performance is excellent. After sintering, the laminated magnetic ring can achieve a better level of current saturation characteristic data under the condition of a high initial magnetic permeability, and can be especially applied to products with high requirements in terms of saturation current after welding, high temperature load characteristics, and inductance change rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ferrite materials, and in particular to a NiCuZn soft ferrite material and a preparation method and application thereof. Background Art

[0002] In the existing technology for upgrading and improving the performance of multilayer ferrite inductor products, the inductance of the device or the magnetic permeability of the core material is mostly controlled as a constant condition. Most researchers improve the current saturation characteristics of the product by changing the shape of the core structure and the design of the internal electrode coil. Although the performance is improved, the modified product cannot fit the existing production process and equipment.

[0003] The application field of NiCuZn soft ferrite has been expanding, and it has also become a basic electronic functional material for chip inductors. The miniaturization and high-frequency process of chip inductors is affected by the update and upgrade of soft ferrite magnetic materials. NiCuZn ferrite core materials with good heat shock resistance, high reliability and high current saturation characteristics are more favored by the market. Low-temperature sintered NiCuZn ferrite has been widely used in multilayer chip inductors. The sintering temperature of NiCuZn ferrite materials prepared by traditional ceramic technology is generally above 1000℃. The sintering temperature is too high and the sintering performance is low. It is difficult to obtain NiCuZn ferrite materials with higher current saturation characteristics. Summary of the invention

[0004] The invention provides a NiCuZn soft magnetic ferrite material and a preparation method and application thereof, so as to provide a NiCuZn ferrite material with good sintering performance and excellent current saturation performance.

[0005] In order to solve the above-mentioned technical problems, one of the purposes of the present invention provides a NiCuZn soft magnetic ferrite material, comprising a main component A and an auxiliary component B accounting for 0.75wt%-1.5wt% of the mass of the main component A; the main component A comprises 65wt%-70wt% Fe2O3, 15wt%-20wt% ZnO, 10wt%-15wt% NiO, 3wt%-10wt% CuO, and 0.05wt%-0.3wt% Co3O4; the auxiliary component B comprises 65wt%-70wt% SiO2, 10wt%-15wt% CaCO3, 10wt%-15wt% Al2O3, and 5wt%-9.5wt% Na2CO3.

[0006] By adopting the above scheme, the present application adds auxiliary component B to the main component A, and the doping amount of auxiliary component B can effectively change the sintering density of the parent phase ferrite material. This effect is caused by the liquid phase sintering mechanism. The glassy material forms a liquid phase during the sintering process, which can greatly reduce the sintering activation energy of the material, thereby promoting the densification of the powder during sintering, so that the NiCuZn ferrite material reaches a higher volume density at a lower temperature. At the same time, changing the component content of the auxiliary component B system material can regulate the micromorphology and organizational structure of the doped parent phase ferrite material, further affecting the electromagnetic physical properties, thereby obtaining an inductor device basic material with fine and uniform organization, high saturation current characteristics and a solder resistance change rate that meets the requirements.

[0007] As a preferred solution, the average particle size of the main component A and the auxiliary component B is 0.5-1.5 μm.

[0008] By adopting the above scheme, the present application controls the average particle size of the main component A and the auxiliary component B within the above smaller range, which can avoid the average particle size of the auxiliary component B being too large, causing the local grain size to become abnormally large, and improve the density of the product.

[0009] In order to solve the above technical problems, the second object of the present invention is to provide a method for preparing a NiCuZn soft ferrite material, comprising the following steps:

[0010] (1) The main component A and the auxiliary component B are mixed, ball-milled, and dried respectively, and then calcined at a high temperature of 800-900° C. and then rapidly quenched to prepare pre-calcined powder A and pre-calcined powder B;

[0011] (2) pre-calcined powder A and pre-calcined powder B are mixed and ball-milled, dried and sieved to obtain a finished powder with an average particle size of 0.5-1.5 μm;

[0012] (3) adding a resin binder, a dispersant, a solvent, and n-propyl acetate to the finished powder, stirring evenly, and casting the resulting film through a casting device;

[0013] (4) stacking the film sheets cast into uniform thickness together, placing them in a specific press for preliminary pressing, and then pressing them into blocks by isostatic pressing, and punching the blocks to form magnetic ring green samples;

[0014] (5) The magnetic ring green body is placed in a furnace for sintering at a temperature of 900-930°C, and the finished product is obtained after cooling.

[0015] By adopting the above scheme, the present application can improve the sintering performance by adding auxiliary component B to the main component A, and control the sintering temperature within the above range, so as to avoid the influence of too low temperature on the formation of crystals and cause too low magnetic permeability, and avoid the deterioration of grain uniformity due to too high temperature. In addition, the sintering time and the holding time are controlled. If the time is too long, the grains will grow abnormally and the grain uniformity will change. Sintering is carried out in air to further ensure that the magnetic ring grains are dense and uniform in size. In addition, the purpose of pre-sintering in the present application is to pre-crystallize the powder. If the pre-sintering temperature is too low, the solid-phase reaction cannot be fully carried out. If the pre-sintering temperature is too high, the optimal sintering temperature will also be higher, which will reduce the sintering performance of the product at a lower sintering temperature, affect the density and average grain size of the product, and have a higher initial magnetic permeability and a lower saturation current.

[0016] As a preferred embodiment, in step (3), every 100 parts by weight of the total powder further includes 20-60 parts by weight of a resin binder, 1-5 parts by weight of a dispersant, 5-15 parts by weight of anhydrous ethanol and 20-35 parts by weight of n-propyl acetate.

[0017] As a preferred solution, any one of the following a)-c) is satisfied:

[0018] a) The resin adhesive is a phenolic epoxy resin, which has good adhesion to the metal oxide substrate and excellent mechanical properties;

[0019] b) The dispersant is a polyacrylic acid polymer, which is a surfactant having two opposite properties, lipophilicity and hydrophilicity, and can rapidly wet the surface of solid particles and raise the energy barrier between solid particles to a sufficiently high level;

[0020] c) The solvent is anhydrous ethanol.

[0021] As a preferred embodiment, in step (1), the calcination time is 1-3 hours; in step (5), the sintering time is 8-15 hours, and the heat preservation time is 2-4 hours.

[0022] As a preferred embodiment, in step (3), the thickness of the diaphragm is 35 μm-45 μm; in step (4), the diaphragm stacking amount is 40-50 layers, and the outer diameter of the magnetic ring green sample is 22-23 mm, the inner diameter is 11-12 mm, and the height is 5-6 mm.

[0023] By adopting the above scheme, the number of diaphragm layers or the total thickness of the bar block is strictly controlled during the preparation process of the present application. A lower number of layers is likely to reduce the flatness of the magnetic ring, while a higher number of layers is likely to cause damage to the magnetic ring during punching.

[0024] As a preferred embodiment, in step (4), the isostatic pressing conditions are 55-65 MPa, 75-85°C for 5 min-15 min.

[0025] As a preferred solution, in step (5), the sintering temperature rise rate is 2.3-2.7°C / min.

[0026] In order to solve the above technical problems, the third purpose of the present invention provides an application of NiCuZn soft ferrite material in the field of chip-type laminated inductors, filters, pulse transformers, magnetic saturation amplifiers, intermediate frequency transformers or chokes.

[0027] Compared with the prior art, the embodiments of the present invention have the following beneficial effects:

[0028] 1. The magnetic permeability, densification degree, microstructure, basic electromagnetic properties and stability of the ferrite material at low temperature sintering temperature are improved in this application, and the sintering performance is excellent. After sintering, the laminated magnetic ring can achieve a better level of current saturation characteristic data while meeting the condition of high initial magnetic permeability. It can be especially used in products with high requirements on saturation current after welding, high temperature load characteristics, inductance change rate, etc.

[0029] 2. The doping amount of the auxiliary component B in the present application can effectively change the sintering density of the parent phase ferrite material, so that the NiCuZn ferrite material can achieve a higher volume density at a lower temperature. The present application further changes the component content of the auxiliary component B system material to regulate the micromorphology and organizational structure of the doped parent phase ferrite material, thereby obtaining a basic material for inductor devices with fine and uniform organization, high saturation current characteristics and a solder resistance change rate that meets the requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 : is an electron microscope image of a magnetic ring cross section of a NiCuZn soft ferrite material in Example 1 of the present invention;

[0031] Figure 2 : It is an electron microscope image of a magnetic ring cross section of a NiCuZn soft ferrite material in comparative example 5 of the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Embodiment 1

[0034] A NiCuZn soft ferrite material comprises a main component A and an auxiliary component B accounting for 0.75wt% of the main component A, wherein the main component A comprises 64.5wt% of iron oxide, 19wt% of zinc oxide, 11.25wt% of nickel oxide, 5wt% of copper oxide, and 0.25wt% of cobalt tetraoxide; and the auxiliary component B comprises 69.9wt% of SiO2, 10.4wt% of CaCO3, 10.2wt% of Al2O3, and 9.5wt% of Na2CO3. The preparation method thereof comprises the following steps:

[0035] (1) After the main component A is mixed evenly, deionized water is added and ball-milled for 12 hours, the material is discharged and dried, and then pre-calcined at 850°C for 2 hours and then rapidly quenched to prepare pre-calcined powder A; after the auxiliary component B is mixed, deionized water is added and ball-milled for 12 hours, the material is discharged and dried, and then pre-calcined at 850°C for 2 hours and then rapidly quenched to prepare pre-calcined powder B.

[0036] (2) 100 g of the weighed pre-calcined powder A was placed in a ball mill, and 0.75 wt % of the pre-calcined powder B was added. 300 g of zirconium balls and deionized water were added. The average particle size of the ball-milled powder was controlled to be 1.0 ± 0.3 μm. After drying, the powder was sieved to obtain a finished powder.

[0037] (3) Casting into a film: For every 100g of finished powder, add 45g of phenolic epoxy resin adhesive, 3.2g of dispersant, 9g of anhydrous ethanol, and 36g of n-propyl acetate. The dispersant is a polyacrylic acid polymer, specifically sodium polyacrylate. After stirring evenly with the equipment, the film is cast into a film with a thickness of 40±5um through a casting machine.

[0038] (4) Molding and sampling: 45 layers of the film with uniform thickness are stacked together and placed in a specific press for preliminary pressing. Then, the film is isostatically pressed for 10 minutes at 60 MPa and 80°C to form a bar block. The bar block is punched out into a specific size magnetic ring sample in a specific size punching die, with an outer diameter of 22.5 mm, an inner diameter of 11.5 mm, and a height of 5±0.5 mm.

[0039] (5) Sintering heat treatment: The ferrite magnetic ring green body is placed in a furnace for sintering. The sintering temperature is 920°C, the temperature rise rate is 2.5°C / min, the sintering time is 12 hours, and the heat preservation is 3 hours. The sintering is carried out in air. After the sintering is completed, it is cooled to room temperature with the furnace.

[0040] Embodiment 2

[0041] A NiCuZn soft ferrite material, wherein each step in the preparation method thereof and the reagents and process parameters used in each step are the same as those in the first embodiment, except that the main component A comprises 64wt% of iron oxide, 19.9wt% of zinc oxide, 10.1wt% of nickel oxide, 5.8wt% of copper oxide and 0.2wt% of cobalt tetroxide.

[0042] Embodiment 3

[0043] A NiCuZn soft ferrite material, wherein each step in the preparation method thereof and the reagents and process parameters used in each step are the same as those in the first embodiment, except that the main component A comprises 67wt% of iron oxide, 15.9wt% of zinc oxide, 12.2wt% of nickel oxide, 4.85wt% of copper oxide and 0.05wt% of cobalt tetroxide.

[0044] Embodiment 4

[0045] A NiCuZn soft ferrite material, wherein each step, reagents used in each step and process parameters in its preparation method are the same as those in Example 1, except that auxiliary component B includes 65wt% SiO2, 12.5wt% CaCO3, 15wt% Al2O3 and 7.5wt% Na2CO3.

[0046] Embodiment 5

[0047] A NiCuZn soft ferrite material, wherein each step in the preparation method thereof and the reagents and process parameters used in each step are the same as those in Example 4, except that the material comprises a main component A and an auxiliary component B accounting for 1 wt% of the main component A.

[0048] Embodiment 6

[0049] A NiCuZn soft ferrite material, wherein each step, reagents used in each step and process parameters in the preparation method are the same as those in Example 1, except that in step (2), the average particle size of the ball-milled powder is controlled to be 2.0±0.3 μm.

[0050] Comparative Example 1

[0051] A NiCuZn soft ferrite material, wherein each step in the preparation method thereof and the reagents and process parameters used in each step are the same as those in the first embodiment, except that the material comprises a main component A and an auxiliary component B accounting for 0.5 wt% of the mass of the main component A.

[0052] Comparative Example 2

[0053] A NiCuZn soft ferrite material, wherein each step in the preparation method thereof and the reagents and process parameters used in each step are the same as those in the first embodiment, except that the material comprises a main component A and an auxiliary component B accounting for 0.1 wt% of the mass of the main component A.

[0054] Comparative Example 3

[0055] A NiCuZn soft ferrite material, wherein each step in the preparation method thereof and the reagents and process parameters used in each step are the same as those in Example 3, except that the material comprises a main component A and an auxiliary component B accounting for 0.1 wt% of the mass of the main component A.

[0056] Comparative Example 4

[0057] A NiCuZn soft ferrite material, wherein each step, reagents used in each step and process parameters in its preparation method are the same as those in Example 1, except that auxiliary component B includes 60wt% SiO2, 15wt% CaCO3, 15wt% Al2O3 and 10wt% Na2CO3.

[0058] Comparative Example 5

[0059] A NiCuZn soft ferrite material includes a main component A, wherein the main component A includes 64.5wt% of iron oxide, 19wt% of zinc oxide, 11.25wt% of nickel oxide, 5wt% of copper oxide, and 0.25wt% of cobalt oxide. The preparation method includes the following steps:

[0060] (1) The main component A is mixed evenly, deionized water is added, and the mixture is ball-milled for 12 hours. The mixture is then dried and pre-calcined at 850° C. for 2 hours and then rapidly quenched to obtain powder A.

[0061] (2) 100 g of the pre-calcined powder A was weighed and placed in a ball mill. 300 g of zirconium balls and deionized water were added. The average particle size of the ball-milled powder was controlled to be 1.0 ± 0.3 μm. After drying, the powder was sieved to obtain a finished powder.

[0062] (3) Casting into a film: For every 100g of finished powder, add 45g of resin binder, 3.2g of dispersant, 9g of anhydrous ethanol, and 36g of n-propyl acetate. Stir evenly with equipment and then cast into a film with a thickness of 40±5um through a casting machine.

[0063] (4) Molding and sampling: 45 layers of the film with uniform thickness are stacked together and placed in a specific press for preliminary pressing. Then, the film is isostatically pressed for 10 minutes at 60 MPa and 80°C to form a bar block. The bar block is punched out into a specific size magnetic ring sample in a specific size punching die, with an outer diameter of 22.5 mm, an inner diameter of 11.5 mm, and a height of 5±0.5 mm.

[0064] (5) Sintering heat treatment: The ferrite magnetic ring green body is placed in a furnace for sintering. The sintering temperature is 920°C, the temperature rise rate is 2.5°C / min, the sintering time is 12 hours, and the heat preservation is 3 hours. The sintering is carried out in air. After the sintering is completed, it is cooled to room temperature with the furnace.

[0065] Comparative Example 6

[0066] A NiCuZn soft ferrite material, wherein each step in the preparation method thereof and the reagents and process parameters used in each step are the same as those in Example 1, except that CaCO3 in auxiliary component B is not added, and the original contents of other components in auxiliary component B are not changed and adjusted to new percentages.

[0067] Comparative Example 7

[0068] A NiCuZn soft ferrite material, wherein each step in the preparation method thereof and the reagents and process parameters used in each step are the same as those in Example 1, except that Al2O3 in auxiliary component B is not added, and the contents of other components in auxiliary component B are not changed and adjusted to new percentages.

[0069] Comparative Example 8

[0070] A NiCuZn soft ferrite material, wherein each step in the preparation method thereof and the reagents and process parameters used in each step are the same as those in Example 1, except that Na2CO3 in auxiliary component B is not added, and the original contents of other components in auxiliary component B are not changed and adjusted to new percentages.

[0071] Comparative Example 9

[0072] A NiCuZn soft ferrite material, wherein each step in the preparation method and the reagents and process parameters used in each step are the same as those in the first embodiment, except that in step (5), the sintering temperature is 1200°C.

[0073] Comparative Example 10

[0074] A NiCuZn soft ferrite material, wherein each step, reagents used in each step and process parameters in the preparation method are the same as those in Example 1, except that in step (1), the pre-calcination temperature of the main component A and the auxiliary component B is 650°C.

[0075] Comparative Example 11

[0076] A NiCuZn soft ferrite material, wherein each step in the preparation method thereof and the reagents and process parameters used in each step are the same as those in Example 1, except that the copper oxide in the main component A is replaced by 99.9% high-purity copper powder of a single element, and the molar amount of copper in the copper oxide in Example 1 is the same as the molar amount of single copper in the 99.9% high-purity copper powder of a single element.

[0077] Comparative Example 12

[0078] A NiCuZn soft ferrite material, wherein each step in the preparation method thereof and the reagents and process parameters used in each step are the same as those in Example 1, except that the nickel oxide in the main component A is replaced by nickel powder containing 99.5% high purity single element, and the molar amount of nickel in the nickel oxide in Example 1 is the same as the molar amount of single nickel in the nickel powder containing 99.5% high purity single element.

[0079] Performance testing

[0080] 1. Saturation current: When current passes through a ferrite ring, magnetic saturation of the magnetic body will occur, and the inductance will decrease. This characteristic is called the DC superposition characteristic. When the sample of the embodiment is tested, the number of coils is 10. The sample is continuously passed with a DC current using an HP4284A_LCR tester, resulting in a decrease in inductance. The current value corresponding to a decrease in inductance of 30% is defined as the saturation current. The ferrite material of the present application requires that the saturation current meet ≥2.2A.

[0081] 2. Density: Use a density balance (analytical balance FA124TC) to test the density using the drainage method. Specific conditions: Boil the magnetic ring in pure water for 2 hours, and then test M 浮 、M 湿 、M 干 According to the density formula ρ=M 干 / (M 湿 -M 浮 ) calculates the density value, where M 浮 M 湿 The value displayed on the balance after the sample is placed in the water cup, M 湿 is the weight of the sample after boiling, M 干 is the weight of the sample after drying.

[0082] 3. Initial magnetic permeability: Use E4991B network analyzer test equipment to test the sample, set the frequency to 4MHz, input the sample outer diameter, inner diameter, and height parameters, and then read the panel data to obtain the sample's initial magnetic permeability value. The initial magnetic permeability required by the product of this application is within the range of 105±10. If the magnetic permeability is too low, the performance value (inductance, impedance) of the product made of the corresponding material (chip-type multilayer inductor device) will be low. Similarly, if the magnetic permeability value is too high, the performance value (inductance, impedance) of the product made of the corresponding material will be high, causing the product performance to exceed the limit and fail.

[0083] 4. Average grain size: Use JSM-6490 scanning electron microscope (SEM) to measure the microscopic morphology of the cross section of the annular sample, use corresponding software to analyze the obtained picture, measure the grain size of the cross section area and calculate the average grain size. The average grain size of the ferrite material in this application should be controlled in the range of 1.0-4.0um. If the size is too small, the heat dissipation of the magnet will be worse, which will lead to failure of the product end life test.

[0084] Table 1 - Performance test results of samples obtained in Examples and Comparative Examples

[0085]

[0086]

[0087] Combined with the performance test results of Example 1 and Comparative Example 5 in Table 1 and Figure 1-2 As shown, attached Figure 1 is an electron microscope image of the sample in Example 1, Figure 2 This is the electron microscope image of comparative example 5 without adding auxiliary component B. The results show that: the magnet of Example 1 has a high degree of densification. The scanning electron microscope image of its magnetic ring cross section shows that the grains are highly uniform, the average grain size is relatively small at about 1.8um, there are no obvious bubbles and pores on the surface of the grains, and the grains at the cross section of the sample have traces of transgranular fracture; while in the sample of comparative example 5 without adding auxiliary component B, its corresponding scanning electron microscope image shows that the magnet grains are larger at 6.82um, the size uniformity is very poor, and there are many bubbles and pores on the surface of the grains, resulting in a low degree of densification of the magnet, and the grains at the cross section of the sample show intergranular fracture.

[0088] By comparing the performance test results of Example 1 and Comparative Examples 6-8 in Table 1, it can be seen that the addition of SiO2 component in the auxiliary component B of the present application can introduce Si atoms into the lattice in the NiCuZn material system to reduce the magnetic permeability, CaCO3 increases the resistivity of the material to reduce losses and increase the operating frequency, Al2O3 can reduce the magnetic permeability and dielectric losses, and Na2CO3 can reduce the pre-sintering temperature and thus improve the sintering performance. According to the combination and specific ratio of the auxiliary component B, the sintering density of the parent phase ferrite material can be effectively changed, so that the NiCuZn ferrite material can achieve a higher volume density at a lower temperature, and the magnetic permeability is maintained in the range of 95-115, so as to obtain a basic material for inductor devices with fine and uniform structure and high saturation current characteristics.

[0089] By comparing the performance test results of Example 1 and Comparative Example 9 in Table 1, it can be seen that a higher sintering temperature will result in a lower density and a larger average grain size of the product, as well as a higher initial magnetic permeability and a lower saturation current. After analysis, it is believed that the density of the magnet is closely related to the sintering temperature curve, and the relationship is nonlinear. When the temperature is high, the thermal energy or excitation energy provided is high, which makes the crystallization state of the magnet more thorough or the crystal structure more disordered. The Cu, Ni, and Zn atoms enter the Fe3O4 spinel structure more fully, and the ionic radius of the three elements Cu, Ni, and Zn is larger than the ionic radius of Fe. After entering the lattice, the unit cell size becomes larger. At the same time, the high temperature makes it easier for the grains to grow, the grain size also becomes larger, and a large number of pores and bubbles appear, causing the overall density of the magnet to decrease. Since there are many Cu, Ni, and Zn ions embedded in the lattice, the unit cell magnetic moment will increase, and the magnetic moment of the magnetic domain will also increase. The magnetic domain will increase as the grain becomes larger. When the magnetic domain is larger, the magnetic dipoles become more. Under the action of the magnetic field H, the magnetic flux lines generated by the magnetic dipoles increase, and the magnetic induction intensity B becomes larger, resulting in an increase in magnetic permeability.

[0090] By comparing the performance test results of Example 1 and Comparative Example 10 in Table 1, it can be seen that if the pre-sintering temperature of the ferrite material raw material in the present application is too low, the powder will not produce pre-crystallization, which will cause the magnetic ring to fail to fully crystallize at the sintering temperature and fail to uniformly nucleate and crystallize, ultimately manifesting as low magnetic permeability, large differences in magnet grains, and inconsistent sizes.

[0091] By comparing the performance test results of Example 1 and Example 6 in Table 1, it can be seen that the larger particle size of the main component A and the auxiliary component B before sintering will lead to a larger average grain size of the final magnetic ring product. Grinding the particle size of the raw material before sintering to below 1.5um helps to reduce the average grain size of the sintered product and improve product performance.

[0092] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a NiCuZn soft ferrite material, characterized in that: The NiCuZn soft ferrite material is composed of a main component A and an auxiliary component B accounting for 0.75wt%-1.5wt% of the mass of the main component A; the main component A is composed of 65wt%-70wt% Fe2O3, 15wt%-20wt% ZnO, 10wt%-15wt% NiO, 3wt%-10wt% CuO, and 0.05wt%-0.3wt% Co3O4; the auxiliary component B is composed of 65wt%-70wt% SiO2, 10wt%-12.5wt% CaCO3, 10wt%-15wt% Al2O3, and 5wt%-9.5wt% Na2CO3; The preparation method comprises the following steps: (1) The main component A and the auxiliary component B are mixed, ball-milled, and dried respectively, and then calcined at a high temperature of 800-900°C and rapidly quenched to prepare pre-calcined powder A and pre-calcined powder B; (2) Pre-calcined powder A and pre-calcined powder B are mixed and ball-milled, dried and sieved to obtain a finished powder with an average particle size of 0.5-1.5 μm; (3) Adding resin binder, dispersant, solvent and n-propyl acetate to the finished powder, stirring evenly and casting into a film through a casting device; (4) stacking the film sheets cast into uniform thickness together, placing them in a specific press for preliminary pressing, and then pressing them into blocks by isostatic pressing, and punching the blocks to form magnetic ring green samples; (5) Place the magnetic ring green body into a furnace for sintering at a temperature of 900-930°C, and obtain the finished product after cooling.

2. The method for preparing a NiCuZn soft ferrite material according to claim 1, characterized in that: The average particle size of the main component A and the auxiliary component B is 0.5-1.5 μm.

3. The method for preparing a NiCuZn soft ferrite material according to claim 1, characterized in that: In step (3), every 100 parts by weight of the total amount further includes 20-60 parts by weight of a resin binder, 1-5 parts by weight of a dispersant, 5-15 parts by weight of a solvent and 20-35 parts by weight of n-propyl acetate.

4. The method for preparing a NiCuZn soft ferrite material according to claim 3, characterized in that: In step (1), any of the following a)-c) is satisfied: a) the resin adhesive is a phenolic epoxy resin; b) the dispersant is a polyacrylic acid polymer; c) The solvent is anhydrous ethanol.

5. The method for preparing a NiCuZn soft ferrite material according to claim 1, characterized in that: In step (1), the calcination time is 1-3 hours; in step (5), the sintering time is 8-15 hours, and the heat preservation time is 2-4 hours.

6. The method for preparing a NiCuZn soft ferrite material according to claim 1, characterized in that: In step (3), the thickness of the diaphragm is 35 μm-45 μm; in step (4), the diaphragm stacking amount is 40-50 layers, and the outer diameter of the magnetic ring green sample is 22-23 mm, the inner diameter is 11-12 mm, and the height is 5-6 mm.

7. The method for preparing a NiCuZn soft ferrite material according to claim 1, characterized in that: In step (4), the isostatic pressing conditions are 55-65 MPa, 75-85° C. for 5 min-15 min.

8. The method for preparing a NiCuZn soft ferrite material according to claim 1, characterized in that: In step (5), the sintering temperature rise rate is 2.3-2.7°C / min.

9. A NiCuZn soft ferrite material prepared by the method for preparing a NiCuZn soft ferrite material according to any one of claims 1 to 8.

10. An application of the NiCuZn soft ferrite material according to claim 9 in the field of chip-type laminated inductors, filters, pulse transformers, magnetic saturation amplifiers, intermediate frequency transformers or chokes.

Citation Information

Patent Citations

  • High-reliability ferrite material and preparation method thereof

    CN110156449A

  • Laminated ferrite inductance material and preparation method thereof

    CN115028443A